Synthesis, characterization, investigation of biological activity and theoretical studies of hydrazone compounds containing choloroacetyl group - Cukurovali, Alaaddin; Yilmaz, Engin (Elsevier, 2014)
In this study, three new hydrazide-hydrazone derivative compounds which contain choloroacetyl group have been synthesized and characterized. In the characterization, spectral techniques such as IR, H-1 NMR, C-13 NMR and UV-Vis spectroscopy techniques were used. Antibacterial effects of the synthesized compounds were investigated against Staphylococcus aureus ATCC 29213, Enterococcus faecalis ATCC 29212, Escherichia colt ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. In the theoretical calculations Gaussian 09 software was used with the DFT/6-31 1+(d,p) basis set. Experimental X-ray analysis of compounds has not been studied. Theoretical bond lengths of synthesized compounds were compared with experimental bond lengths of a similar compound. Theoretical and experimental bond lengths are in good agreement with R2: 0.896, 0.899 and 0.900 for compounds 1, 2, and 3, respectively. For antibacterial activity, the most effective one was found to be N'-(4-bromobenzylidene)-2-chloro-N-(4-(3-methyl-3-phenylcyclobuty1)-thiazol-2-y1) acetohydrazide against P. aeroginaosa ATTC 27853, among the studied compounds. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Hydrazide-hydrazone; Biological activity; Full NBO; IR; DFT